EFFORTS TO IMPROVE CRITICAL THINKING BY USING AUDIO-VISUAL MEDIA - Saiful Muktiali; Nenda Nenda; Siti Juariah; Rini Setyowati (Sean Institute, 2022)
This study aims to determine the audio-visual media in learning to write argumentative texts the pros and cons and to find out the impact of increasing students' critical thinking skills. The research method used is the mix method (mix). This research was conducted at SMK Garuda Nusantara Cikarang with a sample of class X TKR 1 as the experimental group and class X TKJ as the control group. The instruments used in this study were tests in the form of question sheets, observation sheets, and attitude scale questionnaires, as a support for the implementation of learning the application of audio visual media in learning to write argumentative texts for and against their impact on increasing students' critical thinking skills. The instrument is categorized as valid and reliable after being analyzed by expert judgment and statistical tests (validity and reliability). The calculation of this research is through the class average test of pretest and posttest, the number of posttest and posttest scores, knowing the maximum and minimum scores, and test the hypothesis with the paired sample T-Test. The results showed that the activity of students had increased with an average pretest score of 48.88, and an average posttest of 81.00. The impact on increasing students' critical thinking skills after the application of audio-visual media is in accordance with the results of the gain hypothesis test, namely the probability value of Sig. (2-tailed) 0.00 < 0.05. The magnitude of the impact on increasing critical thinking skills is shown by the results of hypothesis testing which states that there are differences in the data from the pretest and posttest results so that there is an increase in learning by looking at the average of each activity. Thus, audio-visual media can be used as an alternative learning media that is used to improve students' critical thinking skills in learning to write pro and con arguments.